An elderly case of malignant small cell glioma with hemorrhage coexistent with a calcified pilocytic astrocytoma component in the cerebellar hemisphere. Issue 5 (31st May 2018) - Sangatsuda, Yuhei; Hata, Nobuhiro; Suzuki, Satoshi O.; Akagi, Yojiro; Hatae, Ryusuke; Kuga, Daisuke; Yoshimoto, Koji; Momosaki, Seiya; Iwaki, Toru; Iihara, Koji
Abstract : Pilocytic astrocytoma is a less aggressive form of glial tumor that commonly occurs in the pediatric population, and its malignant transformation is extremely rare. Here, we report an elderly case of malignant small cell glioma with hemorrhage coexistent with a calcified pilocytic astrocytoma component. An 80‐year‐old male was found to have a right cerebellar non‐enhanced tumor with hematoma adjoining a calcified nodule. The lesion was surgically removed, and a histological examination verified that the tumor was a malignant small cell glioma with hemorrhagic change and the calcified nodule showed features of pilocytic astrocytoma. Genetic analyses revealed no glioma‐relevant genetic alterations such as IDH and BRAF mutations. Although calcification is generally observed in slowly growing gliomas, the aggressive clinical course of calcified cerebellar pilocytic astrocytoma has been previously reported. Our extremely rare case shows that careful follow‐up is necessary even for calcified pilocytic astrocytomas.